Legal Analysis Of Book Piracy - Sigit Ardianto (International Asia Of Law and Money Laundering (IAML), 2022)
Book piracy is an attempt to reproduce a book by printing, photocopying or other means without obtaining written permission from the author and publisher of the related book. The phenomenon of book piracy during the Covid 19 pandemic worsened the asional book industry. Publishers experienced a decline in physical book sales in offline stores, while online sales were overshadowed by the problem of piracy of literacy works in this case books. The ranking of piracy, especially copyright in Indonesia ranks third largest in the world. With the increase in information and technology today, cases of book piracy occur more and more and have increased every year.